1999
DOI: 10.1002/(sici)1097-4547(19990901)57:5<740::aid-jnr16>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Structure, chromosomal localization, and brain expression of human Cx36 gene

Abstract: Rat connexin-36 (Cx36) is the first gap junction protein shown to be expressed predominantly in neuronal cells of the mammalian central nervous system. As a prerequisite for studies devoted to the investigation of the possible role of this connexin in human neurological diseases, we report the cloning and sequencing of the human Cx36 gene, its chromosomal localization, and its pattern of expression in the human brain analyzed by radioactive in situ hybridization. The determination of the human gene sequence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 62 publications
3
26
0
1
Order By: Relevance
“…Cx36 is of interest because its expression is restricted to neurons , and forms only homotypic channels (Al-Ubaidi et al, 2000). Our findings of a decrease in Cx36 expression in trigeminal motoneurons are similar to those of Belluardo et al (2000) showing a decrease in Cx36 mRNA expression in rat spinal motoneurons, but differ from in situ hybridization studies showing a moderate to high density of Cx36 mRNA expression in adult human spinal motoneurons and hypoglossal motoneurons (Belluardo et al, 1999) and rat spinal motoneurons (Chang et al, 1999). Our data regarding the developmental expression of Cx43 in trigeminal motoneurons is similar to that described by Chang et al (1999) for rat spinal motoneurons, but our data for Cx26 and Cx32 expression differs from the results of Chang et al (1999) who reported that Cx32 and Cx26 mRNA were not expressed in spinal motoneurons at any age.…”
Section: Connexin Expression In Trigeminal Motoneuronssupporting
confidence: 66%
“…Cx36 is of interest because its expression is restricted to neurons , and forms only homotypic channels (Al-Ubaidi et al, 2000). Our findings of a decrease in Cx36 expression in trigeminal motoneurons are similar to those of Belluardo et al (2000) showing a decrease in Cx36 mRNA expression in rat spinal motoneurons, but differ from in situ hybridization studies showing a moderate to high density of Cx36 mRNA expression in adult human spinal motoneurons and hypoglossal motoneurons (Belluardo et al, 1999) and rat spinal motoneurons (Chang et al, 1999). Our data regarding the developmental expression of Cx43 in trigeminal motoneurons is similar to that described by Chang et al (1999) for rat spinal motoneurons, but our data for Cx26 and Cx32 expression differs from the results of Chang et al (1999) who reported that Cx32 and Cx26 mRNA were not expressed in spinal motoneurons at any age.…”
Section: Connexin Expression In Trigeminal Motoneuronssupporting
confidence: 66%
“…This region corresponds to the human chromosome 15. Very recently, Belluardo et al (1999) reported that the human Cx36 gene is located on the human chromosome 15q14, to which a juvenile form of myoclonic epilepsy has been mapped. It will be of interest to establish whether mutation(s) in the Cx36 gene cause this form of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…CX36 is expressed throughout the CNS: in the retina, inferior olivary complex, cerebellum, hippocampus, thalamus, striatum, and in the neocortex, particularly in layers IV and VI. [90][91][92][93][94][95] CX36 within the CNS is primarily neuronal 92,96 and appears to be most prevalent in interneruons, 97 although it has also been identified in mouse and human microglia. 98 Coupling between internurons of individual classes 75,99 allows for the control of neuronal oscillations across a wide range of frequencies, and CX36 appears to be important for this.…”
Section: The Relationship Between Oscillations and Behaviormentioning
confidence: 99%